Avaliação do tamanho e estrutura populacional do tubarão lixa (Ginglymostoma cirratum) em recifes costeiros da Paraíba, através do uso de foto-identificação - Araújo, Júlio Lustosa (2018)
The nurse shark, Ginglymostoma cirratum, is a coastal species found in tropical and subtropical waters on the Atlantic Ocean, frequently close to reefs, both coral and rocky. The species was reported as one of the most abundant shark species in coastal waters in Brazil, with the northeastern region possibly holding the greatest numbers of nurse sharks. Despite this, local extirpations and population declines resulted in the evaluation of the species as threatened (Vunerable) in Brazil. The lack of baseline data on its population traits precludes well-elaborated management actions, reinforcing the importance of studies directed to the species. Thus, the objective of this study was to estimate the size and structure of the nurse shark population on coastal reef environments in Paraíba State. Three natural and three artificial reefs were selected based on previous knowledge of nurse shark’s occurrence. Sites were sampled between May 2016 and May 2017. Data recorded included total sharks present during sampling, total of sharks photographed and their estimated total length and sex, as well as water temperature and horizontal visibility. Photographs of the shark’s first dorsal fin were taken and high quality images were used on Interactive Individual Identification System – Contour. Population size estimates were undertaken using Jolly-Seber estimator. Seventeen sharks were positively identified during 38 field excursions, of which 76% were juveniles. There were 36 recaptures of 13 individuals (76% of the total captured sharks) of which 88% were juveniles. The estimator led to an upper population size around 50 individuals, and the population was composed mainly by juvenile sharks, with a sex ratio close to 1:1. The results point to a low population size, however, the high proportion of juvenile individuals probably highlights a sampling error due the limited number of sites and their small geographic range, especially in depth, as all sites were between 12-35m. The high recapture rate emphasizes the site fidelity of the species in the area, which sums up with its low population size to an increased vulnerability. Even though the results are more relevant towards the juvenile size class, they reinforce the need for more populational studies on this endangered species in Brazil, showing as well the need for conservation measures for the species and its environment, particularly on less studied and protected regions, such as Paraíba State.